Peran Media Sosial Bagi Suami Istri dalam Menjalani Hubungan Pernikahan Jarak Jauh - Maulidia Mulyani (State Islamic University (UIN) of Sunan Ampel, 2019)
In the present time the impact of technological progress can be felt in many aspects of life, including marriage. The progress of the development of communication technology has made it easy to communicate specifically for married couples who are undergoing long-distance marital relationships, so that the relationship is maintained and harmonious. Social media is now used as a tool for communication, for example WhatsApp, Line, Facebook, or Instagram. All of those media are used because of their speed in conveying messages, so that long-distance couples can still communicate well and quickly. In a marital relationship, of course, there are fulfillments of rights and obligations. These fulfillments can still be fulfilled through social media, but they are not as maximized as when dealing directly.